1995
DOI: 10.1007/bf03401553
|View full text |Cite
|
Sign up to set email alerts
|

Restricted Usage of T Cell Receptor Vα/Jα Gene Segments with Different Nucleotide but Identical Amino Acid Sequences in HLA-DR3+ Sarcoidosis Patients

Abstract: The finding of V alpha 2.3+ CD4+ lung T cells with identical TCR alpha-chain amino acid sequences but with different nucleotide sequences strongly suggests that different T cell clones have been selected to interact with a specific sarcoidosis associated antigen(s). The identification of T cells with restricted TCR usage, which may play an important role in the development of sarcoidosis, and the possibility of selectively manipulating these cells should have important implications for the treatment of the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 36 publications
2
43
0
Order By: Relevance
“…In early attempts, PCR techniques were applied to address this question, but without any distinct findings [14]. Using new techniques, we initially found a higher-than-normal usage of Vβ22 in lung-accumulated T-cells from HLA-DRB1*03 + patients [16], and in the present report further establish that a substantial part of lung-accumulated Vα2.3 + T-cells also express Vβ22 in HLA-DRB1*03 + patients.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…In early attempts, PCR techniques were applied to address this question, but without any distinct findings [14]. Using new techniques, we initially found a higher-than-normal usage of Vβ22 in lung-accumulated T-cells from HLA-DRB1*03 + patients [16], and in the present report further establish that a substantial part of lung-accumulated Vα2.3 + T-cells also express Vβ22 in HLA-DRB1*03 + patients.…”
Section: Discussionmentioning
confidence: 48%
“…Earlier analyses of the TCR α chain of bronchoalveolar lavage (BAL) Vα2.3 + CD4 + T-cells indicated selection towards specific antigens [14]. Interestingly, HLA-DRB1*0301 and HLA-DRB3*0101 molecules are structurally and functionally similar and seem to present a highly similar peptide antigen repertoire, including identical epitopes [15].…”
Section: Cd4mentioning
confidence: 99%
“…It is essential to remember that the AV2S3+ cell population is not a T-cell clone. The variable a-chain can associate with different variable b-chains [31]. MALLONE et al [32] showed that different T-cell clones can exhibit different avidity towards the same antigen, with the outcome that some clones only proliferate, whereas others both proliferate and produce cytokines in response to a given antigen concentration.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of public TCRs in malignancy was also observed in tumorassociated antigen-specific T cells from melanoma [11][12][13][14][15], synovial sarcoma and prostate cancer [16][17] (Table 1). Public TCRs also occurred in autoimmune diseases such as multiple sclerosis [18], reactive arthritis [9], aplastic anemia [20], psoriasis vulgaris [21], systemic sclerosis [22], sarcoidosis [23], and rheumatoid arthritis [24] (Table 1). In addition, examples of public TCRs were extensively observed in non-human primates and mice [25].…”
Section: Introductionmentioning
confidence: 99%